2019
DOI: 10.1186/s43055-019-0011-1
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lymph nodes: 18F-FDG PET/CT in detection of unusual sites of extranodal lymphoma

Abstract: Background: The purpose of this study was to compare between contrast-enhanced computer tomography (CE CT) and 18 F-FDG PET/CT in the detection of extranodal involvement in lymphoma and to correlate between SUV max of the extranodal lesion and the hottest LN. One hundred patients with pathologically proven lymphoma underwent whole body 18F-FDG PET/CT and CECT scans. Images were compared regarding the ability of detection of extranodal lymphomatous sites. Kappa agreement was applied to find the degree of agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Our results are also matching a study done by Othman et al [14] were 100 patients were enrolled and showed poor agreement between PET/CT and CECTs (k = 0.32).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are also matching a study done by Othman et al [14] were 100 patients were enrolled and showed poor agreement between PET/CT and CECTs (k = 0.32).…”
Section: Discussionsupporting
confidence: 90%
“…The most common involved extranodal organs in our study were lung 19%, GIT (mainly the stomach) 16%, liver 14% and renoadrenal 12%. In Das J et al [22], the most frequently involved extranodal organs were GIT 14.8% (stomach is commonest site), followed by head and neck region 10% (including tonsils, pharynx, tongue, and orbit), lung 8%, and liver 5%, while Othman A et al's [23] study stated that the most common involved extranodal organs were head and neck 18% and GIT 15%. In this study, the organs showing the highest SUV max by PET/CT were lung 44.0, GIT (stomach) 33.4, head and neck (submandibular glands) 32.7, and renoadrenal (kidney) 30.8, while the organs showing the lowest SUV max were chest (thymus 2.80), chest (pleura 5.50), GIT (peritoneum 6.50), and liver 7.00.…”
Section: Regarding Other Extranodal Organ Involvementmentioning
confidence: 94%
“…In agreement with our results, Ricard F et al [18] who stated changes in the staging of 20% of the patients with upstaging in 17% and downstaging in 3% with major changes in 10%. Also, Othman A et al's [23] study mentioned that 10% of the patients were upstaged while 5% were downstaged after PET/CT. Luminari et al [24] resulted that PET/CT helped in upstaging of 11% and downstaging of 1% of patients, while Raanani P et al's [15] study revealed changes in staging of 39% of the patients after PET/CT with 33% upstaging and 6% downstaging.…”
Section: Regarding Lymphoma Staging According To Lugano Classificationmentioning
confidence: 99%
See 2 more Smart Citations